Implementation of The Manpower BPJS Policy in Sidoarjo District: Implementasi Kebijakan BPJS Ketenagakerjaan di Kabupaten Sidoarjo - Omega Puspita; Lailul Mursyidah (Universitas Muhammadiyah Sidoarjo, 2022)
The number of BPJS Employment participants in Sidoarjo Regency experienced a significant decline, especially for non-formal workers in 2018-2019. This condition is inseparable from the policy of implementing employment. This research is a qualitative descriptive study. The research was carried out at the BPJS Employment Office of the Sidoarjo Branch. The focus of this research includes: 1) Implementation of BPJS Employment Policy in Sidoarjo Regency, 2) inhibiting and supporting factors of BPJS Employment Policy Implementation in Sidoarjo Regency. The data of this research are primary and secondary data collected by interview, observation, and documentation. The informants of this research include employees of BPJS Employment in Sidoarjo Regency, and BPJS Employment Participants. Data analysis used Milles and Hubberman qualitative descriptive analysis. The results of the study state that 1) BPJS Employment in Sidoarjo Regency in implementing policies has paid attention to the dimensions of policy implementation, namely communication, resources, disposition and bureaucratic structure. a) Communication, namely in carrying out policy implementation using communication internally and externally smoothly, clearly, and consistently; (b) resources, namely in carrying out policy implementation, competent human resources, quality information, and adequate facilities are supported; (c) disposition, namely in running.